2012
DOI: 10.1097/qai.0b013e318251aedd
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Highly Active Antiretroviral Therapy Versus Highly Active Antiretroviral Therapy and Chemotherapy in Therapy-Naive Patients With HIV-Associated Kaposi Sarcoma in South Africa

Abstract: Background The optimal approach to HIV-associated KS (HIV-KS) in sub-Saharan Africa is unknown. With large-scale rollout of highly active antiretroviral therapy (HAART) in South Africa, we hypothesized survival in HIV-KS would improve and administration of chemotherapy in addition to HAART would be feasible and improve KS-specific outcomes. Methods We conducted a randomized, controlled, open-label trial with intention-to-treat analysis. Treatment-naïve patients from King Edward VIII Hospital, Durban, South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(143 citation statements)
references
References 33 publications
(42 reference statements)
10
128
4
1
Order By: Relevance
“…It was reported that 6.6% of KS patients developed IRIS (4). Furthermore, previous studies demonstrated that KS-IRIS can be serious or even fatal (5). We herein report a case of laryngeal KS that was complicated by IRIS and treated successfully with pegylated liposomal doxorubicin (PLD).…”
Section: Introductionmentioning
confidence: 87%
“…It was reported that 6.6% of KS patients developed IRIS (4). Furthermore, previous studies demonstrated that KS-IRIS can be serious or even fatal (5). We herein report a case of laryngeal KS that was complicated by IRIS and treated successfully with pegylated liposomal doxorubicin (PLD).…”
Section: Introductionmentioning
confidence: 87%
“…There are two small randomized trials that have looked at the role of chemotherapy plus ART and ART alone. The overall response rate of the KS was significantly better for patient in chemotherapy plus the ART group, but there was no overall survival difference between the groups [74,75]. Also we know that HHV-8 is an etiologic agent of virally associated tumors such as Kaposi sarcoma.…”
Section: Electrochemotherapymentioning
confidence: 94%
“…The therapy varies according to the type of KS. In the case of epidemic (HIV-related) or iatrogenic KS, treatment primarily aims at immune reconstitution by means of highly active antiretroviral therapy (HAART) or reduction of immunosuppressive therapy, respectively [11,12].…”
Section: Introductionmentioning
confidence: 99%